An image authentication and recovery scheme based on turtle Shell algorithm and AMBTC-compression - Lin, Chia-Chen; Liu, Xiaolong; Zhou, JianJie; Tang, Chuan Yi (Multimedia tools and applications, 2022)
In the field of digital multimedia, numerous researchers have exploited fragile watermarking for image integrity protection. In order to complete the goals of image authentication and tamper recovery, we propose a fragile watermarking scheme based on turtle shell algorithm and absolute moment block truncation coding (AMBTC) in this paper. The two-layer turtle shell data hiding algorithm is utilized to embed the AMBTC-based recovery bits and CRC-based validation bits into pixel pairs of the image. On the receiver side, after detecting tampered blocks by CRC-based validation bits, the AMBTC-based recovery bits are exploited for tampering recovery. Experimental results demonstrate that our proposed TS-IAR scheme achieves high visual quality of watermarked image while increasing the accuracy of tamper detection with the least false alarm. Furthermore, the average quality of the recovered image provided by the proposed scheme is higher than some representative scheme.